THE ROLE AND FUNCTIONAL DYNAMICS OF WORD GROUPS IN INTERLINGUISTIC RELATIONS - Ulviyya Hajiyeva (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
The development of language is inseparable from interlingual relations. It is an undeniable fact that interlingual relations play a significant and serious role in the development of language. In linguistic literature, interlingual relations are interpreted as changes that occur in one language under the influence of another during the contact of two languages. Although the history of studying interlingual relations and language development issues in linguistics covers a considerable period of time, it has not yet found its full scientific analysis. Therefore, it is one of the urgent problems that needs to be studied. The role of interlingual relations in the development of the mentioned languages ​​is an issue that is absolutely worthy of comprehensive study. There is an urgent need to filter the research devoted to the indicated field, to generalize the ideas formed on the issue, to clarify the conditions and reasons for the emergence of relations between languages, to determine the linguistic and psychological reasons that arise in individual speeches during acquaintance with a foreign language. Two main factors have been identified in the development of languages. They are called intra-linguistic and extra-linguistic factors. Interlingual relations are an external factor of language development. The term interlingual relations itself reflects the mutual relations between languages ​​of the same and different systems. When interconnection between languages ​​continue for a long time, many of the cases of deviation from the language norm become the norm and can gain citizenship in the language. Modern linguistics associates the changes occurring in the scientific language with a number of reasons, a set of reasons. However, there is no unified opinion among linguists on this position” [8, 451]. There is a lot of interest in the problem of language relations, which covers basically all areas of the language. “Scientists who study the problems of language development can be divided into several groups. The first group of scientists includes the romantics, to whom Schlegel and the Grimm brothers, as well as W. Humboldt, belonged. In their opinion, languages ​​that have reached their highest level have lost their beautiful past in connection with the decline of the national spirit” [12, 466]. However, the fallacy of these ideas gives reason to disagree with them.